Comparative study of three heteropolyacids supported on carbon materials as catalysts for ethylene production from bioethanol. Issue 9 (11th April 2017) - Almohalla, M.; Rodríguez-Ramos, I.; Guerrero-Ruiz, A.
Abstract : The efficacy of three different heteropolyacids (HPAs) supported on activated carbon (AC) or on high surface area graphite (HSAG), has been comparatively evaluated in the dehydration of bio-ethanol to yield ethylene or diethyl ether. Abstract : The efficacy of three different heteropolyacids (HPAs) supported on activated carbon (AC) or on high surface area graphite (HSAG) has been comparatively evaluated in the dehydration of bio-ethanol to yield ethylene or diethyl ether. These supported heteropolyacid compounds exhibit remarkable catalytic performances for the ethanol conversion at relatively low reaction temperatures. Furthermore, taking into account the sensitivity of heteropolyacid structures to the presence of water, some catalytic tests with ethanol + water mixtures as the reactant feed have been performed, proving the stability of these composite materials under the used reaction conditions. Structural characterization of these materials has been accomplished by thermal gravimetric analysis coupled with differential thermal analysis (TGA-DTA) and by X-ray diffraction. The textural properties of the synthesized materials were determined from the nitrogen adsorption isotherms. Also, ammonia temperature programmed desorption was performed in order to evaluate the amount and strength of exposed acid surface sites. While phosphomolybdic acid is thermally unstable under the reaction conditions, supported tungstophosphoric and silicotungstic acids are stable under the reaction conditions even in the presence of water. These results are significant because these new carbon supported catalyst materials can be envisaged as highly promising candidates for the production of petrochemicals from bio-ethanol.